The Analisis faktor yang memengaruhi efisiensi kinerja pemeliharaan taman di Hotel Oberoi dan Melia Bali - Valentin, Arista Putri; Widhianthini, Widhianthini; Kohdrata, Naniek (Jurnal Arsitektur Lansekap, 2023)
Analysis of Factors Influencing the Efficiency of the Performance of Garden Maintenance at the Oberoi and Melia Bali Hotels . Hotels on the island of Bali have experienced an increase, that's because more and more tourists are interested in visiting the island of Bali so that a hotel that is indispensable for its existence in the world of tourism has also create business competition. Therefore, the hotel owner's strategy is to attract tourist interest through the arrangement of outdoor aesthetics or gardens. But so that the garden to function optimally, it requires efficient maintenance and can sustainable. Currently, park maintenance activities, especially in hotels, are still fluctuating, that is, they can be very efficient or even less efficient. Destination in this research is to analyze what factors influence efficiency of park maintenance performance in hotels, thus causing occurrence of fluctuations and recommend strategies for management programs garden maintenance. Furthermore, this study uses data analysis techniques using Interpretative Structural Modeling (ISM). Furthermore, from the results of the analysis shows that the most influential factor on performance efficiency garden maintenance is the factor of garden workers and maintaining the cleanliness of the garden area which are in the independent sector which is a key factor that must be resolved soon. Then costs, Standar Operation Procedure (SOP), low quality of human resources, and workers the hotel is in the linkage sector which means it must be handled medium term or after the short term is over.